Royal jelly-derived proteins enhance proliferation and migration of human epidermal keratinocytes in an in vitro scratch wound model - Lin, Yan (BMC Complement Altern Med, 2019)
BACKGROUND: Skin injury is inevitable in daily life. In recent years, with the increasing morbidity of diseases such as diabetes and metabolic disorders, chronic wounds have become a considerable challenge in clinical practice. Royal jelly, reported to have multifarious biological and physiological properties, has been used as a remedy for a variety of wounds since ancient times. However, the active components and mechanisms underlying the wound-healing properties of royal jelly are still largely unknown. METHODS: Water-soluble proteins of royal jelly were fractionated and investigated for the proliferative and migratory effects on human epidermal keratinocytes (HaCaT) in an in vitro wound healing model. The proteins present in bioactive fractions were characterised and quantified using Label-free protein quantification method. The potential functions of these proteins in biological systems were further analysed using bioinformatic tools. RESULTS: A protein fraction, mainly containing major royal jelly proteins 2 (MRJP2), MRJP3 and MRJP7, stimulated proliferative and migratory activities in HaCaT cells without visible cytotoxicity. It exerted the greatest effects on the growth of HaCaT cells in the first 48 h. Furthermore, when treated with this protein fraction, the closure rates of the in vitro scratch wound were significantly increased. Functional analysis indicated that MRJP2, MRJP3 and MRJP7 were associated with carbohydrate transport and metabolism. CONCLUSIONS: We fractionated the water-soluble proteins of royal jelly and identified one fraction (Fraction 2) that induced both proliferative and migratory effects on a human epidermal keratinocyte cell line. Major royal jelly proteins (MRJP2, MRJP3 and/or MRJP7) were speculated to possess potential wound-healing bioactivity. This is the first report that royal jelly may improve wound closure via MRJP-induced cellular proliferation and migration. These proteins may be valuable lead compounds for the development of novel wound healing medications. Our findings would facilitate better understanding of the wound repair mechanisms of royal jelly.